PELATIHAN ARTICULATE STORYLINE BAGI GURU SE-KECAMATAN TAYAN HULU - Ege, Benediktus; Tuah, Yayan Adrianova Eka; Julung, Hendrikus; Huda, Fatkhan Amirul; Duda, Hilarius Jago (STKIP Persada Khatulistiwa Sintang, 2024)
One way to improve the quality of classroom learning is by enhancing teachers' competencies. One aspect that needs improvement is teachers' ability to create learning experiences that utilize applications currently in high demand, such as Articulate Storyline, which can assist teachers in designing creative and innovative media. In Tayan Hulu District, there is a lack of capability among junior high school teachers in using learning media, making it necessary for them to gain knowledge and skills in developing educational media. This training was conducted over one day, providing training and assistance in creating interactive learning media using Articulate Storyline. The training was attended by 19 teachers representing schools in Tayan Hulu District and took place at SMPN 01 Tayan Hulu. From this community service activity, it was found that the average pre-test score of participants was 51.18, and the post-test score was 89.32, indicating that the teachers could follow and understand the material presented by the resource person. It is hoped that the results of this community service activity will enable junior high school teachers to proficiently use the Articulate Storyline application to develop interactive learning media that can be utilized in the teaching and learning process in the classroom